Debt management for development : protection of the poor and the millennium development goals - Raffer, Kunibert (Cheltenham Edward Elgar Publishing Ltd.)
From the British Library catalogue: "Raffer discusses the international debt problem in a profound way and his proposal, the Raffer proposal, is ingenious, practical and wise."
1. Brief history of debt management until 1989 -
2. Briefhistory of debt management after 1989 -
3. In Quest of solutions: sovereign insolvency proposals, collective action clauses and recent country cases --
4. Gleneagles, the multilateral debt relief initiative and the US crisis --
5. The Raffer proposal: an international chapter 9 for countries --
6. Debtor rights and fairness to creditors in rule of Law-based insolvency systems -
7. MDGs, debt distress and poverty: theoretical roots of policies protecting the poor in debtor countries -
8. Poverty, debtor protection and the MDGs -
9. Debt distress, global public goods and a global development; partnership -
10. NGO advocacy for debt reduction cum debtor protection -
11. The Concept of sustainability of international financial institutions -
12. Problems of overoptimism and ownership -
13. MDGs and preferred creditor status -
14. Lending or granting: ODA and the MDGs
Includes bibliographical references (p.278-295) and index.
Keywords: Public finance; EXTERNAL DEBT; DEBT RELIEF; DEVELOPING COUNTRIES; ECONOMICS